Pakistan : Request for Stand-By Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Pakistan's authorities have requested a 23-month Stand-By Arrangement for SDR 5.169 billion in support of their macroeconomic stabilization program. The authorities' program envisages a tightening of fiscal and monetary policies to bring down inflation and reduce the external current account deficit to more sustainable levels. The pace of adjustment seeks to balance the need to address the current macroeconomic imbalances with protecting social stability. The program envisages important reforms in tax policy and administration and public financial management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet